Reconstrução do conceito de intersubjetividade em Hegel - Barbosa, Cleiton Gil (2016)
The issue of intersubjectivity puts Hegel in evidence in the philosophical debate of the contemporary scene. This scenario increasingly abdicates of metaphysical foundations for justification of practices and institutions to justifications that seek the social anchoring. In this sense, Hegel reappears in the contemporary debate due to the characteristic attributed to his writings of youth of theoretical preference for communicative models to think about the social existence of human beings. Intersubjectivity appears in Hegel as a solution to the aporia of the philosophy of subjectivity, which refer to a concept of solipsistic reason unable to think social life organically, but as force and coercion. For Habermas and Honneth there are many fruitful insights in the works of the young Hegel to think reason as having its origin in communicative presuppositions of interaction partners. The dissertation presents the literature on the theme in two general lines which differ themselves on the position of intersubjectivity in Hegel's texts: the first argues that the concept does not solidify along the philosopher's theory, just in your time of youth due to theoretical problems found; while the second understands that Hegel changes, however, does not negate the point of view that is through intersubjectivity that man achieves his own achievement as freedom. Exposing how intersubjectivity behaves in those two moments of the Hegel’s philosophy, reconstruction outlined here argues that Hegel does not abdicate their youth insights on the subject, but rather changes it, in order to overcome the naturalistic grounding of the concept and its extreme connection with classical ethics as seen in youth texts. As shown, the theme change cause the possibility of insert Hegel in the contemporary debate more fruitful than before: with the change, intersubjectivity becomes requisite for the realization of individual free will, whereas the assumptions communicative generated in the interaction become the social and theoretical anchoring in which practices and institutions prove his justice and reason for being. The development of the philosophy of Honneth presents two stages: initially, as it is exposed, he argues that the young Hegel is the only able to provide fruitful insights to contemporary; later, reviewing the work of the mature Hegel, comes to understand that the modern philosopher extends the issue of intersubjectivity and recognition to freedom and its condition. The dissertation seeks to understand the concept of intersubjectivity along the work of Hegel pointing to its theoretical function on each moment as well as the insufficiencies and sufficiency of Hegel's philosophy. Through this cut also it’s understand the thought of Axel Honneth on the theme, as well as the transformation that he operates in his theoretical development.